Apolar Polyisoprenoids Located in the Midplane of the Bilayer Regulate the Response of an Archaeal-Like Membrane to High Temperature and Pressure - LoRicco, Josephine G.; Salvador-Castell, Marta; Demé, Bruno; Peters, Judith; Oger, Philippe M. (Frontiers in Chemistry, 2020)
Archaea are known to inhabit some of the most extreme environments on Earth. The ability of archaea possessing membrane bilayers to adapt to high temperature (>85°C) and high pressure (>1000 bar) environments is proposed to be due to the presence of apolar polyisoprenoids at the midplane of the bilayer. In this work, we study the response of this novel membrane architecture to both high temperature and high hydrostatic pressure using neutron diffraction. A mixture of two diether, phytanyl chain lipids (DoPhPC and DoPhPE) and squalane was used to model this novel architecture. Diffraction data indicate that at high temperatures a stable coexistence of fluid lamellar phases exists within the membrane and that stable coexistence of these phases is also possible at high pressure. Increasing the amount of squalane in the membrane regulates the phase separation with respect to both temperature and pressure, and also leads to an increase in the lamellar repeat spacing of both phases. The ability of squalane to regulate the ultrastructure of an archaea-like membrane at high pressure and temperature supports the hypothesis that archaea can use apolar lipids as an adaptive mechanism to extreme conditions.